2016
DOI: 10.1002/ecs2.1336
|View full text |Cite
|
Sign up to set email alerts
|

Specialization of oribatid mites to forest microhabitats—the enigmatic role of litter

Abstract: The degree of ecological specialization influences the biological performance of species in their natural environment and affects the coexistence of different taxa. However, on a small scale, the diversity of microarthropods that coexist in forest soils and leaf litter seems inordinately high, a situation known as the “enigma of soil animal species diversity”. Since recent studies point to the importance of small‐scale heterogeneity to explain this phenomenon, we use interaction networks between microhabitats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 53 publications
1
26
1
Order By: Relevance
“…Conversely, negative interactions, whether symmetrical or asymmetrical, will result in either niche shifts or checkerboard distributions, according to different or similar ecological species requirements, respectively. A better knowledge of chemical communication systems might thus contribute to explain fine-scale niche segregation (Anderson 1978;Zhao et al 2013) and competition-mediated over-dispersion of functional traits (Widenfalk et al 2016), as observed in soil samples, and then to finally resolve the famous "enigma of soil animal species diversity" (Anderson 1975;Maraun et al 2003;Wehner et al 2016).…”
Section: Ecological and Evolutionary Perspectives In Chemical Communimentioning
confidence: 99%
“…Conversely, negative interactions, whether symmetrical or asymmetrical, will result in either niche shifts or checkerboard distributions, according to different or similar ecological species requirements, respectively. A better knowledge of chemical communication systems might thus contribute to explain fine-scale niche segregation (Anderson 1978;Zhao et al 2013) and competition-mediated over-dispersion of functional traits (Widenfalk et al 2016), as observed in soil samples, and then to finally resolve the famous "enigma of soil animal species diversity" (Anderson 1975;Maraun et al 2003;Wehner et al 2016).…”
Section: Ecological and Evolutionary Perspectives In Chemical Communimentioning
confidence: 99%
“…Adult specimens of Oribatula tibialis (Nicolet) were collected from moss and litter taken from a mixed forest stand near Groß-Gerau, Hesse, Germany, using a thermal-gradient extractor over 24 h (for further methods and habitat characterization, see 44).…”
Section: Methodsmentioning
confidence: 99%
“…The approximately 16,000 described species ( Schatz et al, 2011 ) are collectively ubiquitous, yet individual species are unevenly distributed in all major forests and grasslands, and also in aquatic habitats all over the world ( Wallwork, 1983 ; Schatz, 2005 ; Schatz & Behan-Pelletier, 2008 ). In temperate forests, oribatid mite species tend to inhabit different microhabitat patches and therefore their communities are unequally distributed among mineral soil, litter, mosses, lichens, dead wood or tree bark ( Aoki, 1967 ; Arroyo, Kenny & Bolger, 2013 ; Wehner et al, 2016 ). This specificity may be caused by differences in microhabitat structure (e.g., small vs wide pores, continuous (litter) vs. insular (tree bark, moss); Nielsen et al, 2008 ), microclimatic conditions (e.g., moisture, exposure; Nielsen et al, 2010 ), spatial resource heterogeneity ( Nielsen et al, 2010 ) or biotic interactions (e.g., predation; Hammer, 1972 ; Gao et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, most adult oribatid mite species tend to prefer distinct microhabitats (e.g., litter, moss patches, dead wood, lichens, grassy sods, bark of trees) if conditions are favourable ( Wehner et al, 2016 ). For example, Wehner et al (2016) reported that the microhabitat ‘litter’ provides the most stable ecological conditions and seems to function as habitat for litter specialists (e.g., Hypochthonius rufulus ; Habitat-Hypothesis) and “refuge” for generalists during unfavourable conditions (e.g., Chamobates cuspidatus , Carabodes spp. ; “Connector-Hypothesis”).…”
Section: Introductionmentioning
confidence: 99%